Double-layer magnetized/functionalized biochar composite: Role of microporous structure for heavy metal removals. (February 2021) - Sajjadi, Baharak; Shrestha, Ronish M.; Chen, Wei-Yin; Mattern, Daniell L.; Hammer, Nathan; Raman, Vijayasankar; Dorris, Austin
Abstract: Magnetization facilitates the separation and reuse of adsorbents, but significantly reduces the adsorption capacity. In this study, a double layer magnetized/functionalized biochar composite was synthesized through a hybrid post-pyrolysis magnetization which sustained and even significantly increased the adsorption capacity of microporous carbonaceous biochar (BC). The developed process included i) structural modification of biochar under ultrasound waves, ii) magnetization with magnetite (Fe3 O4 ) nanoparticles, and iii) functionalization with 3-aminopropyltriethoxysilane (TES). Ultrasound irradiation exfoliates and breaks apart the irregular graphite layers of biochar, and creates new, or opens blocked, micropores, thus enhancing the BC's porosity. For its part, TES stabilizes the magnetic nanoparticles on the biochar surface, while it participates in water decontamination through the strong chelation ability of its amino groups toward metal ions. Scanning electron microscopy demonstrated the stable and uniform distribution of Fe3 O4 nanoparticles on the surface of microporous biochar, and Fourier-transform infrared spectroscopy indicated effective surface functionalization. In addition, although magnetization usually reduces the porosity of carbonaceous adsorbents, the ultraviolet–visible spectroscopic analysis showed that double layer magnetic biochar composite exhibited a much greater ability to remove Ni(II) and Pb(II), with 139 % and 38 % higher adsorptions than raw biochar. Almost complete removal of Pb (91 %) was observed by magnetic-BC and the adsorbent could easily be separated using a neodymium magnet. This high performance can be attributed to the synergistic effect of ultrasound activation on increasing the porosity and surface area of biochar along with enhanced chelation imparted by amine functionalization. The developed technique can be used for synthesizing advanced adsorbents for removal of nuclear waste-related metal ions from aqueous environments.